2022
DOI: 10.26434/chemrxiv-2022-s8xc3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of Poly(2-oxazoline)s and poly(2-oxazine)s based formulation library and estimation of polymer/drug compatibility.

Abstract: The main objective of this study is to formulate a library of difficult to solubilize drugs with four slightly different poly(2-oxazoline)s (POx) and poly(2-oxazine)s (POzi) based amphiphilic triblock copolymers and to elucidate whether the drug-polymer compatibility, as estimated by solubility parameters (SPs) might be used as tool to guide formulation development. The theoretical and experimental SPs of different homo-/triblock copolymers and 21 different hydrophobic drugs were calculated by two group contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Micelle LC has been investigated experimentally in great detail for a variety of drugs and pOx/pOzi variants, and a strong dependence on the B block monomer type has been found. [3,12] For example, poly(2-methyl-2-oxazoline) 35 -b-poly(2-propyl-2oxazine) 20 -b-poly(2-methyl-2-oxazoline) 35 -N-Boc-piperazine (A-pPrOzi-A) has been shown to provide drastically superior drug loading for curcumin (CUR), with a LC of 11.9 g L −1 given a polymer feed of 10 g L −1 , in comparison to poly(2-methyl-2-oxazoline) 35 -b-poly(2-butyl-2-oxazoline) 20 -b-poly(2-methyl-2oxazoline) 35 -piperidine (A-pBuOx-A) comprising a constitutional isomer as B block repeat units (LC: 3.2 g L −1 ). [10] The underlying reason for this difference remained unknown until now.…”
Section: Introductionmentioning
confidence: 99%
“…Micelle LC has been investigated experimentally in great detail for a variety of drugs and pOx/pOzi variants, and a strong dependence on the B block monomer type has been found. [3,12] For example, poly(2-methyl-2-oxazoline) 35 -b-poly(2-propyl-2oxazine) 20 -b-poly(2-methyl-2-oxazoline) 35 -N-Boc-piperazine (A-pPrOzi-A) has been shown to provide drastically superior drug loading for curcumin (CUR), with a LC of 11.9 g L −1 given a polymer feed of 10 g L −1 , in comparison to poly(2-methyl-2-oxazoline) 35 -b-poly(2-butyl-2-oxazoline) 20 -b-poly(2-methyl-2oxazoline) 35 -piperidine (A-pBuOx-A) comprising a constitutional isomer as B block repeat units (LC: 3.2 g L −1 ). [10] The underlying reason for this difference remained unknown until now.…”
Section: Introductionmentioning
confidence: 99%
“…51 Assessing polymer-drug compatibility through solubility parameters obtained by group contribution methods has repeatedly provided only very limited predictability. 49,50 Furthermore, for the case of coformulations containing multiple drugs, synergistic and antagonistic effects have been reported. 52 While dissecting the driving polymer−drug interactions for explaining mechanistically the observed differences in LC and LE remains subject to future studies, a recent chemoinformaticsdriven study by Alves et al 35 demonstrated the potential of applying QSPR modeling techniques to predict micelle drug loading.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 The selection of an excipient is not only based on the processability using a given method and the possibility of designing a controlled release from the amorphous formulation, but also the miscibility and possible interactions between the drug and polymer play an important role. 14 Previously, poly(2-oxazoline)/poly(2-oxazine) triblock copolymers have been employed very successfully in high drug loading formulations 15,16 with up to and more than 50 wt% of the drug for a variety of drugs. 17−19 In addition, diblock, random, and gradient copolymers from poly(2-oxazoline)s/ poly(2-oxazine)s have been investigated as potential excipients 20−22 and some systems also allowed high drug loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, poly­(2-oxazoline)/poly­(2-oxazine) triblock copolymers have been employed very successfully in high drug loading formulations , with up to and more than 50 wt% of the drug for a variety of drugs. In addition, diblock, random, and gradient copolymers from poly­(2-oxazoline)­s/poly­(2-oxazine)­s have been investigated as potential excipients and some systems also allowed high drug loadings. …”
Section: Introductionmentioning
confidence: 99%